2019
DOI: 10.3390/ijms20020389
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Bacillus subtilis on Cytokines of Dendritic Cells in Grass Carp (Ctenopharyngodon Idella)

Abstract: Bacillus subtilis is a common group of probiotics that have been widely used in the feed industry as they can increase host resistance to pathogens and balance the immune response. However, the regulatory mechanism of Bacillus subtilis on the host immune system remains unclear in teleosts. In this study, we isolated and enriched dendritic cells from white blood cells (WBCs), and then stimulated them with Bacillus subtilis. Morphological features, specific biological functions, and authorized functional molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Probiotics are capable of controlling cytokines production (pro‐inflammatory and anti‐inflammatory) that balances the immune response (Dong, Rowland, & Yaqoob, 2014; Zhou et al., 2019) However, at present, information on the immunomodulatory effects of C. butyricum on shrimp is scarce. In this respect, the haemolymph inflammatory cytokine parameters (INF‐γ, TNFα, IL‐1, and IL‐6) and intestinal expression of IKK‐β, toll and dorsal genes of M. rosenbergii were tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are capable of controlling cytokines production (pro‐inflammatory and anti‐inflammatory) that balances the immune response (Dong, Rowland, & Yaqoob, 2014; Zhou et al., 2019) However, at present, information on the immunomodulatory effects of C. butyricum on shrimp is scarce. In this respect, the haemolymph inflammatory cytokine parameters (INF‐γ, TNFα, IL‐1, and IL‐6) and intestinal expression of IKK‐β, toll and dorsal genes of M. rosenbergii were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are capable of controlling cytokines production (pro-inflammatory and anti-inflammatory) that balances the immune response (Dong, Rowland, & Yaqoob, 2014;Zhou et al, 2019) butyricum supplementation protected the cells from inflammation that could have resulted in oxidative damage, and also inhibited the activation of the NF-κB signalling pathway. This can be backed by the fact that tumour necrosis factor-alpha (TNF-α), which is a pro-inflammatory cytokine, generated when an acute inflammation happens and is also accountable for multiple cellular signals, leading to necrosis/apoptosis (Beck & Habicht, 1996;Schoenborn & Wilson, 2007;Schroder, Hertzog, Ravasi, & Hume, 2004).…”
Section: Haemolymph Related Immune Parametermentioning
confidence: 99%
“…This work provides the evidence that B. subtilis can directly regulate in ammatory response and lysozyme transcription of zebra sh larvae, suggesting that the immune-activating effect of B. subtilis is self-related. Previous studies also have shown that B. subtilis stimulated dendritic cells of grass carp, and several pro-in ammatory cytokines and antiin ammatory cytokines genes expressions are signi cantly increased (Zhou et al 2019). In addition, the intestinal microbiota induced by dietary additive also has a positive effect on host immune response.…”
Section: Discussionmentioning
confidence: 88%
“…A total of 240 crossbred broiler chickens were randomly allocated into 4 groups with 3 replicates. The groups were named as control group (basal diet), group (BD with 300 g/d BS,1.08×107 CFU/kg), group (BD with 600 g/d BS, 2.16×107 CFU/kg), and group (BD with 900 g/d BS, 3.24×107 CFU/kg). Samples were collected at the 21st day.…”
Section: Abstract Backgroundmentioning
confidence: 99%